4R nutrient stewardship based potassium fertilization for dry-direct seeded rice-wheat cropping system - Vijayakumar, S; Kumar, Dinesh; Jinger, Dinesh; Bussa, Bhargavi; Panda, B B (Indian Farming, 2021)
The technology which saves irrigation water and improves soil health in RWCS is need of the hour. Dry direct-seeded rice is one such technology found gaining importance in IGP. The number of farmers adopting dry DSR cultivation is increasing over the years. However, the productivity of the system is threatened by inefficient nutrient management especially negative K balance and development of multinutrient deficiency. 4R nutrient stewardship based K management in dry DSR-wheat cropping system found increasing the grain yield. Similarly, 4R nutrient stewardship for nitrogen, phosphorus and micronutrient management are developed for different agro-climatic zones. Thus, educating the farmers and extension agent with 4R nutrient stewardship based nutrient management will solve the multiple problems associated with inorganic fertilizer use in RWCS.